How much should we fund the IRS?. (1st July 2021) - Jung, Hanjoon M.; Liang, Meng‐Yu; Yang, C.C.
Abstract: Tax enforcement not only detects tax evasion (the direct effect) but also enforces voluntary compliance (the indirect effect). This paper explores implications of the indirect effect for the optimal size of the budget allocated to the Internal Revenue Service (IRS). The conventional wisdom prescribes that the size of the budget allocated to the IRS should always fall short of the level where an additional dollar allocated would return just an additional dollar of revenue. In a model where taxpayers are subject to a small amount of incomplete information, we show that after taking into consideration the indirect effect of tax enforcement, it is possible that the optimal prescription is opposite to the conventional wisdom.